Challenges in achieving sustainability in Iberian rural areas and small towns: exploring immigrant stakeholders’ perceptions in Alentejo, Portugal, and Empordà, Spain - Morén-Alegret, Ricard (2019)
There is growing evidence of international immigration becoming increasingly influential in peripheral areas in some Southern European countries. Particularly in small localities, where the maintenance of a significant number of active populations is crucial for social, economic and environmental sustainability, immigration can be of vital importance for local and regional policy-making. This paper presents the perceptions, experiences and concerns of various international immigrant stakeholders in Southwest Europe regarding the main challenges in achieving sustainability. Its focus is on rural areas and small towns in Alentejo Litoral (Southwest Portugal) and Alt Empordà (Catalonia, Northeast Spain), places where foreign immigration is above the national average. Using qualitative methods (semi-structured interviews, literature review and participant observation), the main findings show how immigrant stakeholders’ perceptions of local sustainability are rich, engaged and diverse, including interesting differences between some Northwest European immigrants and less advantaged immigrants, e.g. Northwest European immigrants (i.e. British, Germans, French, Dutch, Belgians) stress environmental challenges for sustainability much more than the rest. Overcoming some native prejudices, immigrants in Alentejo Litoral and Alt Empordà also contribute to local knowledge of the ways to achieve dynamic local societies and economies, as well as conserve natural protected areas and agricultural environments.